Approaches to legal governance in constructing Nanhai National Marine Park - Huang, Yuwen; Yu, Minyou (Frontiers in Marine Science, 2025)
As a globally significant marine ecosystem, the South China Sea faces multiple challenges including overfishing, ecological degradation, and geopolitical conflicts. To balance ecological conservation with resource development needs, establishing a South China Sea National Marine Park has emerged as a critical strategy. This paper employs literature analysis, comparative research, and policy evaluation methods to investigate legal governance frameworks for the marine park. The study reveals that China’s current marine conservation legal framework faces challenges such as fragmented legislation, weak enforcement mechanisms, and inadequate integration between international and domestic laws, which hinder cross-border ecological cooperation. To address these issues, the paper proposes enhancing specialized domestic legislation, optimizing enforcement and supervision systems, and promoting regional marine conservation agreements to establish a legal framework tailored to the South China Sea’s unique characteristics. The research also demonstrates that legal development for the marine park must reconcile ecological integrity with geopolitical realities, fostering regional cooperation and trust through legal innovation. This study offers a feasible legal pathway for ecological governance in disputed waters while laying the foundation for sustainable blue economy development.